Behavioral Interventions Associated with Smoking Cessation in the Treatment of Tobacco Use - Roberts, Nicola J. (Libertas Academica, 2013)
Tobacco smoke is the leading cause of preventable premature death worldwide. While the majority of smokers would like to stop, the habitual and addictive nature of smoking makes cessation difficult. Clinical guidelines suggest that smoking cessation interventions should include both behavioural support and pharmacotherapy (e.g. nicotine replacement therapy). This commentary paper focuses on the important role of behavioural interventions in encouraging and supporting smoking cessation attempts. Recent developments in the field are discussed, including ‘cut-down to quit’, the behaviour change techniques taxonomy (BCTT) and very brief advice (VBA) on smoking. The paper concludes with a discussion of the important role that health professionals can and should play in the delivery of smoking cessation interventions.